INTEGRATING VOA LEARNING ENGLISH INTO AN ENGLISH LISTENING CLASSROOM - Hasti Rahmaningtyas; Salma Al Mardhiyyah (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2020)
INTEGRATING VOA LEARNING ENGLISH INTO AN ENGLISH LISTENING CLASSROOMAbstract: Extensive listening is crucial for language development, especially when students’ exposure to the target language is not adequate. This study presents how VOA Learning English website is integrated into an English listening classroom as a listening activity outside the class. Data were collected through questionnaires and learners' extensive listening journal weekly entries, seeking to examine students’ learning experiences and views on experiencing the website. Thirty undergraduate students participated in this study for 14 weeks. Results indicated that learners were satisfied with their learning experience as they had the chance to select materials that they found suitable and appropriate to their proficiency level and interests. Although the students did not enjoy writing the weekly journal assigned after extensive listening, they discovered that learning from VOA Learning English is convenient and useful in enriching their vocabularies and widening their knowledge of the world.Keywords: Extensive listening, VOA Learning English, Listening journalMENGINTEGRASIKAN VOA LEARNING ENGLISH KE DALAM PEMBELAJARAN DI KELASAbstrak: Extensive listening sangat penting dalam pengembangan bahasa, terutama ketika paparan siswa terhadap bahasa target tidak memadai. Penelitian ini menyajikan bagaimana situs web VOA Learning English diintegrasikan ke dalam sebuah kelas Bahasa Inggris sebagai kegiatan menyimak di luar kelas. Data diperoleh melalui penggunaan kuesioner dan jurnal mingguan extensive listening, yang bertujuan untuk memeriksa pengalaman belajar siswa serta pandangan mereka dalam menggunakan situs web tersebut. Tiga puluh mahasiswa program S1 telah berpartisipasi dalam penelitian ini selama 14 minggu. Hasil penelitian menunjukkan bahwa peserta didik puas dengan pengalaman belajar mereka karena mereka memiliki kesempatan untuk memilih sendiri materi yang mereka anggap sesuai dengan tingkat keahlian dan minat mereka. Walaupun siswa tidak benar-benar menyukai kegiatan menulis jurnal mingguan setelah melakukan kegiatan extensive listening yang ditugaskan, mereka mendapati bahwa belajar dari VOA Learning English tidak hanya nyaman tetapi juga berguna dalam memperkaya kosakata mereka dan memperluas pengetahuan mereka tentang dunia.Kata kunci: Extensive listening, VOA Learning English, Jurnal simakan Permalink/DOI: dx.doi.org/10.17977/um015v48i22020p091